2021
DOI: 10.1007/s12207-021-09441-x
|View full text |Cite
|
Sign up to set email alerts
|

The Memory-Undermining Effect of Simulated Crime-Related Amnesia and Its Legal Implications: a Review

Abstract: Pretending to suffer from amnesia for a mock crime has been shown to lead to memory impairments. Specifically, when people are asked to give up their role of simulators, they typically recall fewer crime-relevant details than those who initially confess to a crime. In the current review, we amassed all experimental work on this subject and assessed the characteristics of the memory-undermining effect of simulated amnesia for a crime procedure (i.e., crime stimuli, simulating amnesia instructions, memory tests,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…(2022) and Mangiulli, Riesthuis, et al. (2022): I call for a moratorium of further publications on this topic that do not thoroughly assess alternative explanations, including the possibility of feigning, or that inappropriately minimize or discount such concerns. Failure to do impedes scientific progress and invites a reverberation of the Hess debacle that could haunt forensic psychology and psychiatry for decades.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2022) and Mangiulli, Riesthuis, et al. (2022): I call for a moratorium of further publications on this topic that do not thoroughly assess alternative explanations, including the possibility of feigning, or that inappropriately minimize or discount such concerns. Failure to do impedes scientific progress and invites a reverberation of the Hess debacle that could haunt forensic psychology and psychiatry for decades.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have reported that 9%–93% of defendants charged with a serious crime claim amnesia for the crime (Mangiulli, Riesthuis, et al., 2022) with some writers suggesting that these are valid claims (Bourget et al., 2017; Bourget & Whitehurst, 2007; Bradford & Smith, 1979; Harrison et al., 2017; Hopwood & Snell, 1933; Kopelman, 1995, 2002; Parwatikar et al., 1985; Pyszora et al., 2003, 2014). However, many authors have argued or suggested that most amnesia claims, in the context of criminal charges, are likely feigned (Centor, 1982; Cima et al., 2004; Frederick, 2011; Marshall et al., 2005; McNally, 2004; Merckelbach & Christianson, 2007; Ornish, 2001; Otgaar et al., 2019; Peters et al., 2013; Rubenzer, 2018c), including an entire book (Christianson, 2007) directly on point.…”
Section: Feigned Crime‐related Amnesiamentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, despite the substantial literature on amnesia reported by suspects (e.g., dissociative amnesia, Porter et al, 2001; Taylor & Kopelman, 1984; malingering amnesia, Christianson & Merckelbach, 2004; Mangiulli, Riesthuis, & Otgaar, 2022), the psychologist did not explore this issue. Nor did she address the issue of a probable deficit in encoding abilities, while she mentioned difficulties with short-term memory functions (i.e., “His long-term memory works, but short-term memory is weak”; note that there is no indication in the report that short-term memory and long-term memory were formally tested).…”
Section: Two Cases Of Failure To Use Memory Science By French Expertsmentioning
confidence: 99%